Implikasi Yuridis Penerapan Pasal 130 Ayat (2) Tentang Acte Van Dading Dalam Penyelesaian Mediasi Gugatan Hak Asuh Anak Di Pengadilan Agama - Alfan, Ahmad Syauqy; Huda, Miftahul; Purnamasari, Teti Indrawati (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2023)
This research aims to explain the juridical review of various influencing factors, as well as the urgency of implementing the Peace Deed in resolving Child Custody Lawsuits through Mediation in the Religious Courts by studying the decisions of the Religious Courts in West Nusa Tenggara Province. This type of research is library research. The approach used is normative juridical which also uses a statutory approach, case study and conceptual approach. Data collection techniques were carried out using legal research studies. The primary data for this research is Article 130 HIR, Article 154 RBg KUHPer and PERMA No. 1 of 2016 concerning Mediation Procedures. The secondary data is various literature that is relevant to this research. The results of this research are that there is inconsistency and disharmony between two government regulations regarding the implementation of the Peace Deed in the Religious Courts which involves two regulations and laws, namely Article 130 HIR and Article 154 RBg with PERMA No.1 of 2016 concerning mediation procedures. The inconsistency and disharmony between the two government regulations has resulted in overlapping decisions in the Religious Courts, especially in the case of child custody claims which are listed in several decisions that have been issued by the Religious Courts in several regions in West Nusa Tenggara Province